2009
DOI: 10.7326/0003-4819-150-4-200902170-00003
|View full text |Cite
|
Sign up to set email alerts
|

Safely Ruling Out Deep Venous Thrombosis in Primary Care

Abstract: The Netherlands Organization for Scientific Research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
67
1
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(76 citation statements)
references
References 30 publications
5
67
1
3
Order By: Relevance
“…PTP followed by D-dimer safely ruled out DVT in about 30% of patients with a suspected first episode of DVT. As recently shown in a meta-analysis [2], this outcome was consistent with other similar clinical studies. Table 1 shows patients characteristics.…”
Section: Datasupporting
confidence: 80%
See 2 more Smart Citations
“…PTP followed by D-dimer safely ruled out DVT in about 30% of patients with a suspected first episode of DVT. As recently shown in a meta-analysis [2], this outcome was consistent with other similar clinical studies. Table 1 shows patients characteristics.…”
Section: Datasupporting
confidence: 80%
“…Clinical studies and meta analyses show that algorithms based upon Pre-Test Probability (PTP) assessment and D-dimer safely rule out venous thromboembolism (VTE) when the PTP for the disease is assessed as low and D-dimer is negative [1][2][3]. By these means DVT is ruled out in 30-50% of outpatients with suspected DVT and safely obviates the need for further diagnostic testing [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Point of care D-dimer tests can therefore contribute important information and guide patient management, notably in low risk DVT patients. 4,5 A second example of a near-patient test with immediate consequences for management is the use of point of care C-reactive protein (CRP) testing in lower respiratory tract infections. A recent trial showed a dramatic decrease in antibiotic prescriptions when GPs used CRP testing to guide antibiotic management.…”
Section: Automated Electronic Reminders and Primary Prevention Of Carmentioning
confidence: 99%
“…7 Due to this uncertainty a decision rule specifically for the primary care setting ( Table 1) that includes clinical items and the D-dimer assay result has been developed and validated. 1,8,9 Using this rule, patients in the category of low probability based on the new rule had a 0.7% prevalence of thrombosis. 8 A trial of 1028 patients with suspected DVT using the rule and POC D-dimer test identified 49% of patients at low enough risk to withhold imaging tests (score of ≤3).…”
Section: Previous Research Accuracy Compared To Existing Technologymentioning
confidence: 99%